Prevalensi Nyeri Muskuloskeletal Pada Pengemudi Becak Kayuh Di Palembang - Sugiharto, Henry; Chandra, Novy Rosalia; Legiran, Legiran (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Musculoskeletal system is a system consisting of bones, joints, muscles, tendons and ligaments, that provides body support and facilitates movement. Musculoskeletal pain is defined as persistent or recurring pain that arises as part of a disease process that directly affects the associated bones, muscles, joints or soft tissue. Highest incidence of health problems experienced by workers based on research conducted on 9,482 workers in 12 cities in Indonesia was musculoskeletal disorders (16%). Among various types of work, public transport drivers in various parts of the world have highest prevalence of musculoskeletal pain disorder, ranging from 53% to 91%. A descriptive cross-sectional study design ofpedicab rickshaw driverswas conducted at Kemuning District, Palembang. Primary data were collected by interviews and simple neurological clinical examinations. All data was processed using SPSS 22 for windows. The results found highest prevalence of musculoskeletal pain in people older than 51 years (60%) and affected 74.3% of subject who worked as pedicab rickshaw drivers. Most subject (77.2%) have a normal body mass index. From this study, we found that lower extremities were the most common site of musculoskeletal pain (77.1%) with 64.7% subject reported a mild pain intensity.